Persistence Strategies in Adult Literacy Programs Supported by Community Colleges - Renata Russo; Mary V. Alfred (Adult Education Research Conference, 2008)
This roundtable will focus on the reasons why adult learners persist long enough to obtaining a post-secondary degree or certification. Furthermore, this study in progress is investigating the impact adult literacy and GED transition programs have on adult learners in post-secondary education.
Keywords: adult literacy; GED; community college; persistence; transition